Genotyping by Sequencing for SNP-Based Linkage Analysis and Identification of QTLs Linked to Fruit Quality Traits in Japanese Plum (Prunus salicina Lindl.) - Salazar, Juan A.; Pacheco, Igor; Shinya, Paulina; Zapata, Patricio; Silva, Claudia; Aradhya, Mallikarjuna; Velasco, Dianne; Ruiz, David; Martínez-Gómez, Pedro; Infante, Rodrigo (Frontiers in Plant Science, 2017)
Abstract Marker-assisted selection (MAS) in stone fruit (Prunus species) breeding is currently difficult to achieve due to the polygenic nature of the most relevant agronomic traits linked to fruit quality. Genotyping by sequencing (GBS), however, provides a large quantity of useful data suitable for fine mapping using Single Nucleotide Polymorphisms (SNPs) from a reference genome. In this study, GBS was used to genotype 272 seedlings of three F1 Japanese plum (P. salicina Lindl) progenies derived from crossing ‘98-99’ (as a common female parent) with ‘Angeleno’, ‘September King’ and ‘September Queen’ as male parents. Raw sequences were aligned to the Peach genome v1, and 42,909 filtered SNPs were obtained after sequence alignment. In addition, 153 seedlings from the ‘98-99’ × ‘Angeleno’ cross were used to develop a genetic map for each parent. A total of 981 SNPs were mapped (479 for ’98-99’ and 502 for ‘Angeleno’), covering a genetic distance of 688.8 cM and 647.03 cM, respectively. Fifty five seedlings from this progeny were phenotyped for different fruit quality traits including ripening time, fruit weight, fruit shape, chlorophyll index, skin color, flesh color, over color, firmness and soluble solids content in the years 2015 and 2016. Linkage-based QTL analysis allowed the identification of genomic regions significantly associated with ripening time (LG4 of both parents and both phenotyping years), fruit skin color (LG3 and LG4 of both parents and both years), chlorophyll degradation index (LG3 of both parents in 2015) and fruit weight (LG7 of both parents in 2016). These results represent a promising situation for GBS in the identification of SNP variants associated to fruit quality traits, potentially applicable in breeding programs through MAS, in a highly heterozygous crop species such as Japanese plum.